A Review on Stress, Stressors-Their Effects and Adaptive Response - Vasudev V; Girish V; Ravindra K N (Disease and Health: Research Developments Vol. 9, 2025)
Stress, derived from the Latin ‘Stringere,’ meaning to draw tight. Stress is the physiological and psychological reactions of the organisms to forces of a deleterious nature that tend to disturb its normal equilibrium. Even though understanding of stress started in the 17th century itself, it has changed rapidly through centuries with changes in the conditions of life and circumstances. Selye (1956), the ‘father of stress, researching stress, coined the terms ‘eustress’ and ‘distress’ to designate positive and negative stresses, respectively. Further, it is classified into physical stress, psychological stress, psychosocial stress, behavioral stress, physiological stress, immunological stress, etc., depending on the pressure on the life of a human being. Selye in 1975 proposed the phenomenon known as ‘general adaptation syndrome,’ which is also known in the literature as ‘Selye syndrome.’ Nonetheless, Selye (1975) also coined the term stressor to refer to the causative event or stimulus as opposed to the result of stress. Whether it is an intrinsic or extrinsic stressor, it results in disease, and this diseased condition may be due to the involvement of genes. Thus, there is genomic instability in the form of chromosomal aberrations, and the frequency of this has been shown to increase dramatically due to anthropogenic activities in the 21st century. However, nature has gifted the biological systems to overcome this problem with mechanisms called genetic repair mechanisms. One such mechanism is called adaptive response. This phenomenon has been observed from viruses to humans, thus universal in nature. All the above aspects are explained in detail, and befitting conclusions are given in this review paper to further understand the intricacies involved in stress, its genetics, and their implications.